Pembuatan Website Biro Pendidikan Nurul Jadid dengan Sistem Framework sebagai Media Informasi Pendidikan di Pesantren - M Syafiih; Muhammad David Abdullah; Moch Ryan Purwanto; Mohammad Jafar Shodiq; Mohammad Hijrah; Moh Alif Putra Mawardi; Muhammad Yudi Nasirudin (Universitas Nurul Jadid, 2021)
The Nurul Jadid Islamic Boarding School Education Bureau is one of the bureaus in charge of implementing education for Elementary Secondary Schools (DASMIN), which is fully responsible to the head of the pesantren. The work program carried out by the education bureau includes: (1) making the Annual Budget Needs Plan (RKAT) for primary to secondary schools, the work programs of all schools will be discussed at the beginning of each year to be used as a reference as the education bureau policy. (2) Take full responsibility for the implementation of Teaching and Learning Activities (KBM) of all formal schools in Nurul Jadid Islamic Boarding School. (3) As an evaluation and monitoring agency for Teaching and Learning Activities (KBM) in formal schools at the Nurul Jadid Islamic Boarding School Foundation. The Framework-based Education Bureau Web Application as an information medium in the Education Bureau needs and must be understood by all stakeholders in the Education Bureau, so there is a need for socialization and training of web applications at the Education Bureau. The training is very helpful in understanding the functions and benefits of the information web application at the Education Bureau. The targets of the training are all elements in the Education Bureau, school principals, school operators and IT managers in all schools in the Nurul Jadid Islamic Boarding School Foundation area.